Changes in Soil Nitrate and Ammonium During the Corn Growing Season as Affected by Nitrification Inhibitors - F. D. Hansel; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2019)
Nitrification inhibitors (NI) are used to delay the nitrification process, increasing nitrogen fertilization efficiency. The objective of this study was to evaluate the effect of NI on soil nitrate (NO3-N) and ammonium (NH4-N) content throughout the growing season for corn. The study was conducted at four locations (Manhattan, Scandia, Rossville, and Ashland, KS) during the 2017 and 2018 crop seasons. Most of the NI effects on soil NH4-N and NO3-N were observed early in the season and when the higher nitrogen (N) fertilizer rate was used. An increase in NO3-N soil content was observed during the season with a posterior decrease at the end. At the V8 corn growth stage, we observed the peak of NO3-N soil content at 0- to 12-in. sampling depth with an additional increase at 12- to 24-in. depth in the treatment without NI, suggesting NO3-N movement to the lower soil layer or uptake by the corn crop.
Keywords: nitrogen fertilization; corn; nitrification process